Betulin alleviated ethanol-induced alcoholic liver injury via SIRT1/AMPK signaling pathway. (March 2016) - Bai, Ting; Yang, Yong; Yao, You-Li; Sun, Peng; Lian, Li-Hua; Wu, Yan-Ling; Nan, Ji-Xing
Graphical abstract: Abstract: The present study was conducted to investigate the protective effect of betulin, a triterpene from the bark of Betula platyphylla Suk, against ethanol-induced alcoholic liver injury and its possible underlying mechanisms. In vitro, human hepatic stellate cell line, LX-2 cells were treated with betulin (6.25, 12.5 and 25 μM) prior to ethanol (50 mM) for 24 h. Cell viability was analyzed by methyl thiazolyl tetrazolium assay, protein expressions were assessed by Western blot. In vivo, we induced alcoholic liver injury in male C57BL/6 mice, placing them on Lieber-DeCarli ethanol-containing diets for 10 days and then administering a single dose of ethanol (5 g/kg body weight) via gavage. Betulin (20 and 50 mg/kg) were given by gavage every day. In vitro results showed that betulin effectively decreased LX-2 cell viability, attenuated collagen-I, α-smooth muscle actin (α-SMA) levels, activated liver kinase B-1 (LKB1) and adenosine monophosphate-activated protein kinase (AMPK) phosphorylation. Betulin suppressed the expression of sterol regulatory element-binding protein-1 (SREBP-1), and genetic deletion of AMPK blocked the effect of betulin on SREBP-1 in ethanol treated LX-2 cells. In vivo, betulin attenuated the increases in serum aminotransferase and triglyceride levels in the mice fed with chronic-binge ethanol, while significantly inhibited SREBP-1 expression and activated LKB1-AMPK phosphorylation. Additionally, betulin enhanced the sirtuin 1 (SIRT1) expression mediated by ethanol. Taken together, betulin alleviates alcoholic liver injury possibly through blocking the regulation of SREBP-1 on fatty acid synthesis and activating SIRT1-LKB1-AMPK signaling pathway.